Effect of Ovulation Induction on Ovarian Histologies in a Rat Model - Ulusoy, Özlem; Güven, Davut; Süllü, Yurdanur; Erdoğan, Özgür; Kılıço, İsmail; Üstün, Cazip; Koçak, İdris (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: To examine the effect of human menopausal gonadotropin(HMG) and follitropinBeta (rFSH) on the ovarian histologies in a rat model. STUDY DESING:Thirty-nine female, one-year old rats were enrolled for the trial. They were divided into three groups. In the first group, 13 rats received, six cycles of ovulation induction with human menapausal gonadotropin.In the second group, 13 rats received six cycles of ovulation induction with folitropin beta the third study group consisted of 13 rats which received six cycles of saline intramuscularly. RESULT: The mean number of the cells that stained positive for Ki-67 was 42.3±20.6, 44.9±27.3and 42.5±24.8 in the folicles, respectively.The mean number of cells that stained positive for Ki-67 in epithelium was 0.15±0.42, 0.04±0.14,0.05±0.18, respectively. The mean dysplasiascore was 2.46±2.10, 1.69±13 and 1.62±1.89 in the ovarian epithelial cells respectively. CONCLUSION:Development of malignant lesion were not found in any of the rat ovaries after ovulation induction. As a result of this study, we found out that human menapausal gonodotropin and folitropin beta used in treatment of infertility, when administered for six cycles in accordence with the dosage determined, do not have the potential to develop neoplasia in rats.